Nurses' perception of viral hepatitis screening in primary health care (Research, Society and Development, 2022)
Objective: To analyze the perception of nurses in the screening of viral hepatitis in Primary Health Care (PHC). Methods: This is an action research developed in Ananindeua, State of Pará and approved by the Ethics Committee under opinion number: 5,081,537. Data collection was carried out from August 2021 to February 2022 with professional Nurses from the Family Health Strategy-FHS, through the application of a semi-structured questionnaire containing ten items on sociodemographic and work characterization and Likert scale of 5 points in which participants could classify their knowledge about 16 (sixteen) questions regarding the participants’ attibutions, in accordance with Technical Note No. 369/2020-CGAHV/DCCI/SVS/MS, which deals with strategic expansion of the Brazilian population’s access to the diagnosis of viral hepatitis and referral of detected cases for treatment. Results: The study covered 20 professionals, most of them female (95%). 100% of he research participants approved the importance of knowing the epidemiological profile of their assigned area population and recognized the importance of identifying the existence of pregnant women with hepatitis B and /or C and the mandatory notification of viral hepatitis. As for vaccination coverage, only 1% of respondents were undecided about its importance. Conclusion: In view of the professional nurses various attributions in PHC, it was possible to identify that is necessary to create strategies that facilitate the management of the time of these professionals to work in the dimension of the care production and tracking of viral hepatitis, being able to dedicate more time to this activity and provide comprehensive care to the user in a more qualified way, accompanying them throughout the care flow with prevention, promotion and treatment actions, and thus, contributing to universal coverage and access, providing meaning to the relationship between health services and community individuals, as well as contributing to universal health coverage and access.